GASTRECTOMY WITH OMENTUM PRESERVATION VS GASTRECTOMY WITH OMENTECTOMY FOR LOCALLY ADVANCED GASTRIC CANCER : A SYSTEMATIC REVIEW - Sandy, Risko; Ayu Dwinastiti, Yasmine; Sudarsa, ⁠I Nyoman (Journal of Advanced Research in Medical and Health Science (ISSN 2208-2425), 2023)
Background: Gastric cancers can be divided into the intestinal type and diffuse type. The most common underlying etiology of intestinal-type carcinoma is Helicobacter pylori infection, which can develop into atrophic gastritis with intestinal metaplasia. Complete omentectomy is considered to be essential in the radical gastrectomy for gastric cancer (GC), but its clinical benefit remains unclear. The aim: This study aims to show about gastrectomy with omentum preservation vs gastrectomy with omentectomy for locally advanced gastric cancer. Methods: By comparing itself to the standards set by the Preferred Reporting Items for Systematic Review and Meta-Analysis (PRISMA) 2020, this study was able to show that it met all of the requirements. So, the experts were able to make sure that the study was as up-to-date as it was possible to be. For this search approach, publications that came out between 2013 and 2023 were taken into account. Several different online reference sources, like Pubmed and SagePub, were used to do this. It was decided not to take into account review pieces, works that had already been published, or works that were only half done. Result: In the PubMed database, the results of our search brought up 104 articles, whereas the results of our search on SagePub brought up 77 articles. The results of the search conducted for the last year of 2013 yielded a total 88 articles for PubMed and 48 articles for SagePub. The result from title screening, a total 7 articles for PubMed and 28 articles for SagePub. In the end, we compiled a total of 10 papers. We included five research that met the criteria. Conclusion: Laparoscopic treatment of gastric cancer with D2 lymphadenectomy and omentum preservation is safe and feasible, both for EGC and for AGC. Total omentectomy may be avoided in tumors smaller than 5.25 cm and T1/T2 tumors. However, lymph node metastasis in the greater omentum is associated with recurrence in the peritoneum, liver, ovary and death.